Fermentação alcoólica com leveduras de características floculantes em reator tipo torre com escoamento ascendente - Pacheco, Thályta Fraga (2010)
Ethanol has been considered an alternative biofuel to replace oil reducing environmental and energy problems in the world. The Brazilian sugar industry believes that it will be one of the world's largest suppliers of alcohol fuel and technology to other countries. Therefore, technologies that improve the performance of the sector output gain importance in the country. Thus, in this work was studied the ethanol fermentation using upflow tower reactor with external recirculation and one strain of yeast with flocculent characteristics. It was evaluated the ethanol yield, productivity and the residual sucrose concentration through a central composite design (CCD), in which the percentage of cells in the inoculum ranged from 4.7 to 45.3%, sucrose concentration from 100 to 220 g/L and the recycle flow rate from 2.6 to 17.1 mL/s as variables. All experiments were conducted until the complete consumption of medium sucrose, however it was chosen seven hours for analysis of responses in the CCD. The strain did not show ability to form flakes well defined, but presented capacity of sedimentation. The recirculation stream exerted little influence on the analyzed responses. These were heavily influenced by the inoculum cell concentration. The responses were also influenced by initial sucrose concentration. It was evaluated two conditions of maximum responses, one by an analysis of response surfaces (45% of cells in the inoculum, initial sucrose concentration 200 g/L and recirculation flowate of 15 mL/s) and the other by the yield stationary point (33% of cells in the inoculum, initial sucrose concentration in 180 g/L and recycled flow of 12.7 mL/s). The yield stationary point was the best condition among those evaluated to conduct an alcoholic fermentation using this strain and reactor configuration under study. It was obtained in this experiment, an ethanol yield of 98%, productivity of 13.4 gethanol/L.h and a residual sucrose concentration of 3.1 g/L. The models obtained by the response surface presented a good reproducibility, as predicted, for this case, a 100% of yield, 13.5 g/L.h for ethanol productivity and the residual sucrose concentration of 7.4 g/L. A kinetic study of fermentation was realized on the optimized conditions by experimental design. The Tosetto kinetic model was adjusted to the experimental results. The ethanol fermentation in tower reactor using the strain of yeast with flocculent characteristics presented a greater productivity and higher yield when compared to data reported in the literature or in the industrial processes for ethanol production.